Mastering scale and complexity in software reuse : 16th International Conference on Software Reuse, ICSR 2017, Salvador, Brazil, May 29-31, 2017, Proceedings /: 16th International Conference on Software Reuse, ICSR 2017, Salvador, Brazil, May 29-31, 2017, Proceedings. (2017) - Unknown
No abstract available